Analysis and comparison of the goalkeeper's role in past and modern soccer: a pilot study - Altavilla, G. (Journal of Physical Education and Sport, 2023)
In modern soccer, performance control and regulation are regarded as relevant methodological procedures to maximize match performance results. Speaking of the role and technical-tactical quality among different generations of goalkeepers, they are often referred to a comparison based on personal beliefs and not on scientific data analysis evaluation. The purpose of the pilot study is to compare the technical and tactical performance of some elite goalkeepers, in two time periods and in different championships (Italian and European). Such comparison has been performed through a scientific analysis of the data collected to verify if there have been any significant changes on the tactical function of today's goalkeepers compared to the past. Data was collected both from the match and analysis the interactive online football video library (www.footballia.net), which has an archive of over 15.000 games. Therefore, it was possible to carry out a careful observation and evaluation of the matches and specific technical actions of the goalkeepers. Eight goalkeepers participated in this study and they have been divided into two groups (Group A: Donnarumma, Reina, Neuer and Ter Stegen; Group B: Zoff, Rossi, Buffon and Tafarel). The information was collected concerning six professional goalkeepers: two Italians and four foreigners. The goalkeepers have been chosen, analysed and evaluated on six matches played from each of them, detecting the data related to ball management and the position of goalkeepers in the court in 540 minutes of match. In modern football the goalkeeper has a fundamental tactical role which requires, in addition to the protection of his own goal area, also the coverage of a much wider field area.